Sistemas agroflorestais em assentamentos rurais: uma contribuição para a construção de sistemas produtivos sustentáveis? Uma visão a partir dos agricultores - Gomes, Haroldo Borges [UNESP] (2013)
Brazilian agriculture has a history of social and productive exclusion beyond the sustainable exploitation of natural resources. Degradation and fragmentation of natural ecosystems, with significant reduction of biodiversity, have become increasingly subject of scientific and political discussions. New production systems for family farms have been proposed by civil society organizations, universities and other institutions to mitigate the effects of this process on biodiversity . One of systems has been the focus of analysis of this work. The Project Coffee with Forest, developed by the Institute for Ecological Research , sought to create islands of biodiversity within agricultural plots in rural settlements in the Pontal do Paranapanema Region, São Paulo State, Brazil. This project aims to contribute to the recolonization of isolated forest fragments, increasing gene flow and species genetic diversity of the species . At the same time generates income for the involved families and new forms of sustainable production. The objective of the research was to analyze the production characteristics and families who have adopted the agroforestry project Coffee with forest and the possible contribution of these systems to build sustainable models of production, through the analysis of the perceptions of the producers participating in the project. This study consisted of a questionnaire to 25 producers (50 % of the total) who implemented the shade grown coffee units. It was found that among the producers surveyed, most have over 60 years of age and, although all develop agricultural activities on the lot, most families get non-agricultural incomes worth more than the income from productive activities. The results indicated that the vast majority of producers surveyed considered that the Project Coffee with Forest , although it occupies only a small area of the lot , brought improvements to the ...